PREVALANCE OF PREMENSTRUAL SYNDROME AND KNOWLEDGE ASSESSMENT REGARDING IT’S PREVENTION AMONG MEDICAL STUDENTS OF A PRIVATE MEDICAL COLLEGE OF ISLAMABAD: Premenstrual Syndrome And It’s Knowledge - Kalsoom, Dr Umay; Sultana, Abida; Amjad, Tahira; Bairam, Saima (Pakistan Armed Forces Medical Journal, 2018)
Objective: To assess prevalence of premenstrual syndrome (PMS) in medical students and to determine their knowledge regarding its prevention. Study Design: A cross sectional study. Place and Duration of Study: This study was conducted at Foundation University Medical College, Islamabad, from Jun to Aug 2017. Material and Methods: A purposive sample of 359 female medical students was taken after applying selection criteria. After ethical approval and consent of respondents, data was collected through self-administered structured questionnaire on demographic variables, prevalence of PMS, physical, psychological and behavioral changes, knowledge regarding its prevention etc. Data was analyzed by SPSS version 20. Frequencies were computed and descriptive statistics applied. Cross tabulation between knowledge regarding prevalence of premenstrual syndrome and prevention of premenstrual syndrome was done. Pearson Chi Square test was applied to see the association between these two variables. Cochran test of conditional independence was applied to see conditional association between these variables at p-value <0.05. Result: PMS was found in 280 (80%) students. Out of them, 266 (95%) experienced physical changes and breast tenderness was the most common 159 (60%). While 210 (75%) had psychological changes and depression was found in 76 (36%). Behavioral changes were present in 120 (43%) and most prevalent was effect on academic performance which was 88 (76%). About 250 (71.5%) were ignorant about its prevention while only 100 (28.5%) knew about its prevention. Statistically significant association was found between knowledge regarding prevention of premenstrual syndrome and presence of premenstrual syndrome, as p-value 0.00 of Pearson Chi- Square 35 at df1 was less than 0.05. On application of Cochran test of conditional independence, significant conditional association was found between these variables as p-value of 0.00 was <0.05. Conclusion: Premenstrual Syndrome was found in majority of the students while knowledge about its prevention was low. Its effect on academic performance was agreed by majority of students. Awareness activities should be undertaken about the syndrome and its prevention. The subject should be given importance especially in the curriculum of medical education.